An Psoriasis In HIV Patients: A Paradox: Psoriasis In HIV Patients: A Paradox - Damayanti, Nita; Pudjiati, Satiti (Journal of Pakistan Association of Dermatologists, 2022)
Introduction: Human immunodeficiency virus (HIV) infection is associated with increased susceptibility to skin disorders, including psoriasis. The exacerbation of psoriasis in severe advanced HIV is paradoxical. Case: a 26-year-old man with HIV who had been diagnosed with psoriasis ten months before the diagnosis of HIV. The skin biopsy results indicated psoriasis vulgaris with a tissue CD4/CD8 ratio of 0/34. The initial CD4 count was 130 cells/L. The patient received ARV and topical steroids. There was a clinically significant rise in blood CD4 and tissue CD4/CD8 ratio in three-month follow-up. Discussion: There are several hypotheses was proposed to explain the pathophysiology of psoriasis in HIV. The main therapy of psoriasis with HIV is ARV. Conclusion: HIV can induce or as a risk factor of psoriasis. It’s important to do a search further for risk factors in sexually transmitted diseases in patients with severe and recalcitrant psoriasis. The main therapy of psoriasis with HIV is ARV.